PREVALENCE AND RISK FACTORS OF DIABETIC NEUROPATHY IN TYPE II DIABETES PATIENTS A CROSS-SECTIONAL STUDY - RUDRA NARAYAN DASH; PRABHUDATTA MOHAPATRA; N. SAROJ KUMAR CHOUDHURY; KARMAJEET RATH; DURGA MADHAB KAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Diabetic neuropathy (DN) is often underdiagnosed and undertreated, underscoring the importance of identifying risk factors in high-risk groups. This study examines the prevalence and risk factors of this condition in type II diabetes patients to enhance prevention and management strategies. Methods: This cross-sectional study, conducted in Bhubaneswar, evaluated a total of 450 patients with type 2 diabetes mellitus (T2DM). The research gathered comprehensive data on demographics, clinical conditions, and lifestyle factors of the participants. The findings revealed that DN was present in 180 patients, accounting for 40% of the sample, whereas 270 patients, or 60%, did not exhibit any signs of the condition. Results: This study of 450 T2DM patients revealed that 40% had DN, particularly among those with poor glycemic control (HbA1c >7.5%: 64.7%) and diabetes duration over 5 years (OR 2.75, p<0.001). Key risk factors included smoking (OR 3.55, p<0.001), alcohol use (OR 2.89, p<0.001), and hypertension (OR 2.45, p=0.002). Common symptoms were tingling (77.8%), numbness (66.7%), shooting pain (55.6%), and muscle weakness (44.4%), highlighting the need for improved glycemic control and lifestyle changes. Conclusions: The research highlights the link between DN and factors like poor blood sugar control, long-term diabetes, and unhealthy habits. Timely screening, effective management, and lifestyle changes are crucial to mitigating its effects.